The effect of partial substitution of polyphosphates by aluminium hydroxide and borates on the technological and fire properties of medium density fibreboard. Issue 6 (2nd November 2022) - Martinka, Jozef; Mantanis, George I.; Lykidis, Charalampos; Antov, Petar; Rantuch, Peter
ABSTRACT: Aim of this study was to evaluate the effect of aluminium hydroxide and borates, separately or combined with ammonium polyphosphate (APP), upon the technological and fire properties of medium density fibreboard (MDF). Fire resistant MDF was fabricated in the laboratory from Scots pine ( Pinus sylvestris L.) fibres bonded with a high molar ratio melamine-urea-formaldehyde resin. Overall, 24 h-swelling and water absorption properties of the treated boards were improved or remained unchanged compared to untreated ones. On the contrary, the internal bond strength (IB) of the fibreboards was significantly reduced up to 48%. The fire properties of the fibreboards were assessed by the determination of limiting oxygen index and cone calorimetry. As expected, the tested fire-retardants improved the fire resistance of the boards. Furthermore, the combination of aluminium hydroxide with ammonium polyphosphate considerably upgraded the fire retardancy while the incorporation of borates into APP showed much weaker effects.